Sensitivity of the phenoxy derivatives of 2,4-dihydro-5H-[1,2,3]triazolo[4,5-d]pyrimidin-5-ones to acidic and basic stimuli - Alexander K. Eltyshev; Nataliya P. Belskaya (Chimica Techno Acta)
Herein we report the research on the sensitivity of six hydroxy derivatives of dihydrotriazolopyrimidines (HO-DTP) to acids and bases. The UV/Vis and fluorescence spectra of these compounds were investigated with the addition of the acids and bases. Spectral data revealed the strong red shifts for emission and absorption maxima in the presence of KOH and NaOH. Moreover, two DTPs demonstrated strengthening of the emission intensity. The obtained results and data published in our previous paper demonstrated the strong and selective sensory response of DTPs to the acids and bases and elucidated relationships between the structure and sensitivity to the environment. This finding allowed us to manage these properties by introducing the combination of substituents and functionalities into the heterocyclic core. Thus, investigations demonstrated the potential of the application of DTPs as chemo- and fluorosensors for selective detection of acids and bases.